Only for genius -(-2)⁴ + 2² : (-2) (2°+1) - (-2²) = 32 + 4 : (-2) (1+1) - (4) = 32 + (-2) (2) - (4) = 32 + (-4) - (4) = 32 - 4 - 4 = 24
Triunghiu:
-(-2)⁴ = - 32.........Rezultat final =40
Răspunsuri la întrebare
Răspuns de
3
Răspuns
Explicație pas cu pas:
- ( - 2 )⁴ + 2² : ( - 2 ) x ( 2⁰ + 1 ) - ( - 2² ) = - 16
= - 16 + 4 : ( - 2 ) x ( 1 + 1 ) - ( - 4) =
= - 16 + ( - 2 ) x 2 + 4 =
= - 16 - 4 + 4 =
= - 16
Răspuns de
3
Alte întrebări interesante
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă